1997
DOI: 10.1074/jbc.272.36.22381
|View full text |Cite
|
Sign up to set email alerts
|

Negative Regulation of Mitogen-activated Protein Kinase Activation by Integrin αIIbβ3 in Platelets

Abstract: Activation of the mitogen-activated protein (MAP) kinase pathway in nucleated cells is dependent on both growth factor receptors and integrins engaged in cell adhesion. Human platelets are an interesting model for studying cell adhesion and the involvement of integrin engagement on extracellular signal-regulated kinase (ERK) activation, independently from the nuclear-DNA signal pathway. Maximal phosphorylation and activity of ERK2 occurred late during thrombin-induced platelet aggregation (90 s and later), an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
2
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 29 publications
6
39
2
1
Order By: Relevance
“…This is consistent with previous report that association of αIIbβ3 with fibrinogen inhibits ERK activation in platelet [21]. It was reported that the increase in PP2A activity induced by EGF results in inhibition of ERK2 activity in A431 cells [9].…”
Section: Discussionsupporting
confidence: 82%
“…This is consistent with previous report that association of αIIbβ3 with fibrinogen inhibits ERK activation in platelet [21]. It was reported that the increase in PP2A activity induced by EGF results in inhibition of ERK2 activity in A431 cells [9].…”
Section: Discussionsupporting
confidence: 82%
“…We have yet to formally assess the stoichiometry of this association, but preliminary studies suggest that the majority of the ␣ IIb ␤ 3 molecules are not bound to PP1c. Nevertheless, our data show that this association regulates MLC phosphorylation, and others (19,20) have reported serine/threonine de- ) MLC (ppMLC) or MLC. B, platelets were treated with either Me 2 SO or 250 nM okadaic acid (OA) and aggregated using thrombin.…”
Section: Resultsmentioning
confidence: 67%
“…Dephosphorylation Signals by Integrin ␣ IIb ␤ 3 via an Associated PP1 33041 phosphorylation of extracellular signal-regulated kinases ERK (19) and Jun-N kinase JNK (20) upon fibrinogen binding. More importantly, these transient dephosphorylation events are essential for platelet physiology because phosphatase inhibitors impair platelet aggregation, adhesion, and spreading to fibrinogen (21,22).…”
Section: Resultsmentioning
confidence: 99%
“…In platelets, ERKs have been shown to be activated after stimulation by thrombin, 13 collagen, 14 or phorbol esters 15 as well as to play a role during store-mediated Ca ϩϩ entry. 16 ERK2 was also shown to be downregulated by ␣ IIb ␤ 3 engaged in ligand binding or aggregation, 17 and a recent study indicated that von Willebrand factor binding to glycoprotein Ib-IX leads to ␣ IIb ␤ 3 activation via ERK2. 18 However, the upstream effectors and the downstream targets of the platelet ERK signaling pathway remain largely uncharacterized.…”
Section: Introductionmentioning
confidence: 99%